(NaRMQNSKIJ WOPROS I POLITIKA rOSSII (B( 1915-1917 (NGG(B.) /s - d; (NtUNQN(B, (NwALERIJ gEORGIEWI^s; d; (NmUZEJ(B-(NINSTITUT GENOCIDA ARMQN nan ras; (NsO@Z ARMQN rOSSIIs ((NeREWAN (B:s (Nmiga nan ra(B,s, 2003)
(NrEZ(B.: (NANGL(B. ( (NS(B.465-472 ).s
(NbIBLIOGR(B. (NW PODSTRO^(B. (NPRIME^(B. (NI S(B. 473-481 ( 154 (NNAZW(B. )s
Keywords: (NaRMQNSKIJ WOPROSs -- 1915-1917 (NGG(B.s; (NiSTORIQ aRMENIIs; (NrOSSIQs -- (NpOLITIKAs -- 1915-1917 (NGG(B.s; (NgENOCID ARMQN W tURCIIs -- 1915-1917 (NGG(B.s; (NrUSSKO(B-(NARMQNSKIE POLITI^ESKIE OTNO[ENIQs -- (NnA^ALO (BXX (NW(B.s